President Zviad Gamsakhurdia’s Caucasian Policy in the Context of Abkhaz-Georgian and Ossetian-Georgian Conflicts - Gvantseladze, Teimuraz (Actual Problems of Kartvelology, 2019)
The present article tells about the contacts maintained by its author (Member of the Subcommittee on Ethnic Relations of the Supreme Council of the Republic of Georgia) with North Caucasian national movements in the context of Abkhaz-Georgian and Ossetian-Georgian relations. Based on facts, the article suggests that the government of the USSR tried to prevent Georgia from becoming independent in every possible way. It deliberately created problems between the Georgian authorities on the one hand, and the Abkhazian and Ossetian sides on the other hand. In this context, it was especially significant to neutralize pro-separatist sentiments in the North Caucasus and to explain the true state of affairs regarding Abkhaz-Georgian and Ossetian-Georgian relations in Georgia.